2016
DOI: 10.1177/0148607115625621
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Body Composition Changes in Women Following Roux‐en‐Y Gastric Bypass Surgery

Abstract: BACKGROUND Although most individuals experience successful weight loss following Roux-en-Y gastric bypass (RYGB), weight regain is a concern, the composition of which is not well-documented. Our aim was to evaluate changes in body composition and handgrip strength as a measure of functional status in participants from a previous 1-year post-RYGB longitudinal study who had undergone RYGB approximately 9-years prior. METHODS Five women from an original larger cohort were monitored pre-RYGB and 1.5-months, 6-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…We found that the highest rates of FFM loss were observed at 3 and 6 months post-surgery, and a plateau phase was reached at 18 months post-surgery. Our findings align with previous studies reporting substantial FFM loss at 6 months post-surgery with little change up to 12 months post-surgery [17,18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the highest rates of FFM loss were observed at 3 and 6 months post-surgery, and a plateau phase was reached at 18 months post-surgery. Our findings align with previous studies reporting substantial FFM loss at 6 months post-surgery with little change up to 12 months post-surgery [17,18].…”
Section: Discussionsupporting
confidence: 93%
“…14% of the patients exceeds the 35%FFML/WL threshold at 36 months post-surgery). Although no previous studies assessed prevalence of excessive FFM loss, substantial amounts of FFM loss with large variation between individuals have been reported in other studies [17][18][19]. These findings suggest that FFM loss is not sufficiently tackled by post-bariatric care.…”
Section: Discussionmentioning
confidence: 85%
“…The systematic search resulted in 302 eligible articles in PubMed, 507 articles in Embase, and 315 articles in Web of Science. After removal of duplicates and elimination based on the selection criteria, 59 studies were included in risk and bias assessment and quantitative analyses (Figure 2), with 37 studies assessing LBM, 11,16-51 20 studies assessing FFM 22,25,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] , and 3 studies assessing SMM. [71][72][73] The subanalysis on type of surgery was performed on 52 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The population of participants had a mean age of 44 years, and no documented differences were observed in weight loss results or comorbidity resolution. Bariatric surgery leads to loss of fat mass 394 , alters gut hormones 395 and can exacerbate weight loss-induced sarcopenia 396–398 and osteoporosis 399402 . Carefully designed studies are needed before promoting this intervention.…”
Section: Future Directions and Emerging Therapiesmentioning
confidence: 99%